2019
DOI: 10.1007/s10461-019-02703-5
|View full text |Cite
|
Sign up to set email alerts
|

Transgender Women’s Concerns and Preferences on Potential Future Long-Acting Biomedical HIV Prevention Strategies: The Case of Injections and Implanted Medication Delivery Devices (IMDDs)

Abstract: There are several long-acting biomedical HIV prevention products in the development pipeline, including injections and implanted medication delivery devices (IMDDs). It is critical to understand concerns and preferences on the use of these products in populations that shoulder a disproportionate burden of the HIV epidemic, such as transgender women. This will allow researchers and public health professionals to construct interventions tailored to the needs of these women to promote optimal use of these tools. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…These Standards of Care pertain to prepubescent gender diverse children and are based on research, ethical principles, and accumulated expert knowledge. The principles underlying these standards include the following 1) childhood gender diversity is an expected aspect of general human development (Endocrine Society and Pediatric Endocrine Society, 2020 ; Telfer et al., 2018 ); 2) childhood gender diversity is not a pathology or mental health disorder (Endocrine Society and Pediatric Endocrine Society, 2020 ; Oliphant et al., 2018 ; Telfer et al., 2018 ); 3) diverse gender expressions in children cannot always be assumed to reflect a transgender identity or gender incongruence (Ehrensaft, 2016 ; Ehrensaft, 2018 ; Rael et al., 2019 ); 4) guidance from mental health professionals (MHPs) with expertise in gender care for children can be helpful in supporting positive adaptation as well as discernment of gender-related needs over time (APA, 2015 ; Ehrensaft, 2018 ; Telfer et al., 2018 ); 5) conversion therapies for gender diversity in children (i.e., any “therapeutic” attempts to compel a gender diverse child through words, actions, or both to identify with, or behave in accordance with, the gender associated with the sex assigned at birth are harmful and we repudiate their use (APA, 2021 ; Ashley, 2019b , Paré, 2020 ; SAMHSA, 2015 ; Telfer et al, 2018 ; UN Human Rights Council, 2020 ).…”
Section: Chapter 7 Childrenmentioning
confidence: 99%
“…These Standards of Care pertain to prepubescent gender diverse children and are based on research, ethical principles, and accumulated expert knowledge. The principles underlying these standards include the following 1) childhood gender diversity is an expected aspect of general human development (Endocrine Society and Pediatric Endocrine Society, 2020 ; Telfer et al., 2018 ); 2) childhood gender diversity is not a pathology or mental health disorder (Endocrine Society and Pediatric Endocrine Society, 2020 ; Oliphant et al., 2018 ; Telfer et al., 2018 ); 3) diverse gender expressions in children cannot always be assumed to reflect a transgender identity or gender incongruence (Ehrensaft, 2016 ; Ehrensaft, 2018 ; Rael et al., 2019 ); 4) guidance from mental health professionals (MHPs) with expertise in gender care for children can be helpful in supporting positive adaptation as well as discernment of gender-related needs over time (APA, 2015 ; Ehrensaft, 2018 ; Telfer et al., 2018 ); 5) conversion therapies for gender diversity in children (i.e., any “therapeutic” attempts to compel a gender diverse child through words, actions, or both to identify with, or behave in accordance with, the gender associated with the sex assigned at birth are harmful and we repudiate their use (APA, 2021 ; Ashley, 2019b , Paré, 2020 ; SAMHSA, 2015 ; Telfer et al, 2018 ; UN Human Rights Council, 2020 ).…”
Section: Chapter 7 Childrenmentioning
confidence: 99%
“…In addition, the lack of information on the characteristics and effects of this drug reduced the confidence in LAI-PrEP’s protection and efficacy [ 24 , 29 ] and increased the individual’s fear on the effects of using a higher medication dosage compared with oral PrEP [ 22 , 24 , 26 , 27 , 30 ]. Among the participating TGW, this concern or skepticism about the effects of LAI-PrEP stems from the possible interference with feminizing hormone therapy ( [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show some specificities and congruence in relation to the findings of qualitative and quantitative studies that analyzed the use of alternative methods for the daily usage of PrEP pill. In this sense, the profile and identification of participants as vulnerable adolescents is the highlight of the study; looking at the panorama of quali-quantitative research, only a few studies contemplate this target audience [22][23][24][25][26], consider transgender [27,28], consider previous PrEP usage experience [29], determine the level of PrEP adherence [26], or take into account the first experiences of using LAI-PrEP [23,30].…”
Section: Discussionmentioning
confidence: 99%
“…Although these outcomes may not present a barrier to use for these men, this is not the case for all potential users. For example, other studies have shown that some transgender women were concerned that mild scarring and other skin-related reactions related to potential future PrEP implants could become serious [ 40 , 41 ]. Thus, it may be necessary to engage novel strategies to communicate actual risk [ 41 ], as some populations may overestimate this.…”
Section: Discussionmentioning
confidence: 99%
“…For example, other studies have shown that some transgender women were concerned that mild scarring and other skin-related reactions related to potential future PrEP implants could become serious [ 40 , 41 ]. Thus, it may be necessary to engage novel strategies to communicate actual risk [ 41 ], as some populations may overestimate this. Icon arrays, which communicate risk using graphical representations of icons symbolizing people affected by a given outcome (eg, circles), may be one such strategy [ 42 ].…”
Section: Discussionmentioning
confidence: 99%